Investigating how early academic performance and parental socio-economic status predict and explain successful completion of secondary education in Germany - Bittmann, Felix (Frontiers in Education, 2024)
In educational sociology, it is of greatest interest to explain why some students are more successful than others and obtain higher educational qualifications or receive better grades, which can have longlasting consequences. The present study compares the influence of early academic performance, which can be regarded as a proxy of overall intelligence, to the socio-economic status (SES) of the family, which measures how much a family can invest in the education of their offspring. Using largescale German NEPS panel data (N=5,208), the analyses test statistically how much variance of two outcome variables (acquisition of higher education eligibility and final grade) are explained by academic performance and SES; both measured approximately nine years earlier at the beginning of secondary education. Dominance analyses reveal that performance has a larger influence (ca. 14% for both outcomes) than SES (ca. 8% for eligibility and ca. 4% for grades). Regression analyses show that high performance can better compensate for low SES than vice versa. These results indicate that performance is probably more relevant for academic success than the SES of one's own family.Acknowledgments: earlier versions of this paper have been presented in two research colloquia, where I received valuable feedback (Colloquium Empirical Social Research in Konstanz / Weekly Doctoral Seminar in Bamberg). I want to thank all participants for their helpful comments. In addition, two reviewers gave helpful comments.